Les biocides dans les collections – persistances toxiques, relectures critiques et nouvelles pratiques - Lucie Monot; Isabel Garcia Gomez; Lotte Arndt (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
In this interview, the authors (two curator-restorers at the Musée d'ethnographie in Geneva, and a museology researcher) examine museum conservation practices and their aims in the light of the means employed and their sometimes unexpected effects. While chemical treatments of collections were intended to stabilise the material condition of artefacts, their toxic effect on professionals, the objects themselves and the public concerned was often not taken into account when they were used. From a broader decolonisation perspective, the question arises as to how conservation-restoration can help to move beyond unilateral decision-making on the part of museum professionals to ensure that the choices of the people and communities concerned are heard and prioritised.